CRACKS IN THE GREAT WALL: ZERO-COVID PROTESTS AND THE REASSERTION OF POLITICAL SECURITY IN CHINA - Pandjaitan, Khannia Zhafira Ronaulli; Sudirman, Arfin (Universitas Padjadjaran, 2026)
The protests of the zero-COVID policy in 2022, which led to the issuance of Ten New Measures in China, are an interesting political phenomenon to study. This phenomenon raises questions about the dynamics of China’s political security during the zero-COVID policy period and how the government responded to the social pressures that arose. Applying political security theory that emphasizes national objectives, threat perceptions, and political freedom of action, this article analyzes China’s political dynamics during that period. This article concludes that political security for a country is often realized through various actions justified to protect national interests and maintain social stability and harmony to strengthen political legitimacy. In maintaining political legitimacy during the Covid-19 pandemic, the Chinese government demonstrated political security stability through issue framing strategies, mass mobilization, a punishment and reward approach, and optimization of the economic sector and nationalism. Meanwhile, the phenomenon of protests of the zero-Covid policy contributed as one of the supporting factors, but not a determining factor, in the change of Covid-19 policy in China. Thus, the dynamics that occurred did not indicate a change in the political system, but rather the political impact that emerged during that period.